Preparing meetings and conferences - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training)
Preparing the manager to attend the meeting and conference. Planning the meetings and conference with 6 Ps:proper, planning, present, particularly, poor and performance.
Copy available in DVD format
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Meetings -- Planning; Congresses and conventions -- Planning; Business meetings